2016
DOI: 10.1039/c6nj01956k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity of some novel piperazinophanes with an intraannular ester functionality

Abstract: Ester based 1 : 1 and 2 : 2 oligomeric piperazinophanes were synthesized using a multicomponent reaction (MCR) technique and assessed for their antibacterial activity and further supported by molecular docking studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, phenols have usually been converted to their corresponding aryl C-O electrophiles, such as fluoroalkylsulfonates [ 4 , 5 ], sulfamates [ 6 , 7 , 8 ], sulfonates [ 9 , 10 , 11 , 12 ], carbonates [ 13 , 14 , 15 ], carbamates [ 16 , 17 ], ethers [ 18 ], phosphoramides, phosphonium salts, phosphates, and pivalates [ 19 , 20 , 21 , 22 ]. Besides the preferable availability of phenol derivatives, this method also proves to be cost-effective, as well as an efficient reaction route to form C-C bonds, C-N bonds, and C-H bonds ( Scheme 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 ]. Phenolic esters, a type of aryl C-O electrophiles, are considered as notable functional groups or protecting groups in organic synthesis, and can be found in various bioactive natural products, agrochemicals, pharmaceuticals, and functional polymers [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, phenols have usually been converted to their corresponding aryl C-O electrophiles, such as fluoroalkylsulfonates [ 4 , 5 ], sulfamates [ 6 , 7 , 8 ], sulfonates [ 9 , 10 , 11 , 12 ], carbonates [ 13 , 14 , 15 ], carbamates [ 16 , 17 ], ethers [ 18 ], phosphoramides, phosphonium salts, phosphates, and pivalates [ 19 , 20 , 21 , 22 ]. Besides the preferable availability of phenol derivatives, this method also proves to be cost-effective, as well as an efficient reaction route to form C-C bonds, C-N bonds, and C-H bonds ( Scheme 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 ]. Phenolic esters, a type of aryl C-O electrophiles, are considered as notable functional groups or protecting groups in organic synthesis, and can be found in various bioactive natural products, agrochemicals, pharmaceuticals, and functional polymers [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esters have been determined to be one of the most noteworthy functional groups in organic synthesis, found in various bioactive natural products, agrochemicals, pharmaceuticals, and functional polymers. Traditionally, phenol esters could be achieved by the reaction between phenols and carboxylic acid derivatives in the presence of a large amount of bases, exhibiting several disadvantages. The direct oxidative esterification would express more effective synthetic procedures for the production of phenol esters. , Cheng et al previously reported a Pd­(OAc) 2 -catalyzed esterification reaction of aldehydes with arylboronic acids under air to form phenol esters . Wu et al demonstrated a Pd 2 (dba) 3 -catalyzed production of phenol esters via the decarboxylative coupling of isatoic anhydrides with arylboronic acids under an oxygen atmosphere .…”
Section: Introductionmentioning
confidence: 99%